Fundamental immunology - Paul, William E. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
Suitable for graduate students, post-doctoral fellows, basic and clinical immunologists, and any physician treating diseases in which immunologic mechanisms play a role, this title offers extensive coverage of molecular biology that explains the molecular dynamics underlying immune disorders and their treatment